2017
DOI: 10.1264/jsme2.me16132
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Flooding and the <i>nosZ</i> Gene in Bradyrhizobia on Bradyrhizobial Community Structure in the Soil

Abstract: We investigated the effects of the water status (flooded or non-flooded) and presence of the nosZ gene in bradyrhizobia on the bradyrhizobial community structure in a factorial experiment that examined three temperature levels (20°C, 25°C, and 30°C) and two soil types (andosol and gray lowland soil) using microcosm incubations. All microcosms were inoculated with Bradyrhizobium japonicum USDA6 T , B. japonicum USDA123, and B. elkanii USDA76 T , which do not possess the nosZ gene, and then half received B. diaz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
2

Relationship

4
5

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 44 publications
3
18
0
Order By: Relevance
“…This signifies that cultural management such as waterlogging may affect the population dominance of strains belonging cluster Bd110. This result is supported by our previous reports where it was observed that the dominance of cluster USDA110 T was enhanced by flooding condition in the soil (37) and that USDA110 cluster are dominant on fine-textured soil that are affected by water status and oxidation-reduction potential in the soil (36). Additionally, it was reported that the anaerobic condition in flooded soil of alluvial origin resulted in the dominance of USDA110 T (43) which is also similar our results.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This signifies that cultural management such as waterlogging may affect the population dominance of strains belonging cluster Bd110. This result is supported by our previous reports where it was observed that the dominance of cluster USDA110 T was enhanced by flooding condition in the soil (37) and that USDA110 cluster are dominant on fine-textured soil that are affected by water status and oxidation-reduction potential in the soil (36). Additionally, it was reported that the anaerobic condition in flooded soil of alluvial origin resulted in the dominance of USDA110 T (43) which is also similar our results.…”
Section: Discussionsupporting
confidence: 90%
“…By far, diverse species of bradyrhizobia were reported to be micro-symbionts of soybean such as and (3, 8, 16, 20, 34, 51, 55). Accordingly, many reports stated that soil pH, salinity, climate and cultural management influence the diversity and distribution of soybean bradyrhizobia (1, 5, 11, 22, 24, 37, 44, 54). High diversity of microorganisms in the soil plays an important role in maintaining soil health and vast, accurate information about this could lead to better crop productivity.…”
Section: Introductionmentioning
confidence: 99%
“…These findings suggested that B. diazoefficiens ( nosZ + ) is predominant in Gleysol soils and B. japonicum ( nosZ − ) in Andosols ( 23 ). Saeki et al ( 18 ) recently indicated that the possession of nosZ confers a competitive advantage to B. diazoefficiens in flooded soil; this is consistent with the predominance of nosZ + bradyrhizobia in Gleysol soils ( 23 ). Thus, the aim of the present study was to identify key physiological traits in denitrification that differentiate the distribution of B. diazoefficiens and B. japonicum in soybean fields in Japan.…”
mentioning
confidence: 62%
“…Our findings show that denitrification processes were initiated in the T0 site, representing the starting point of primary succession, as evidenced by the predominance of Mesorhizobium in the early stages (0 and 20 years); this genus has a strong nitrogen fixation ability and promotes plant growth (Velez et al, 2017). At the T2 site, Brachybacterium was the dominant genus, with a high nitrogen fixation and denitrification capacity; it mostly grows in acidic-neutral soil (Saeki et al, 2017). Pseudomonas was found in the three sites T0, T1, and T2; it has the ability to degrade cellulose, produce amylase, and dissolve calcium phosphate, and based on its antibacterial properties, it has a certain certain inhibitory effect on soil diseases (Meyer et al, 2017;Ramette et al, 2006;Almario et al, 2014).…”
Section: Variation In Nosz Denitrifying Bacterial Communities In Respmentioning
confidence: 68%